Pertimbangan Hukum Hakim Terhadap Pelaku Tindak Pidana Perkosaan (Studi Putusan Nomor 451/Pid.B/2021/PN Amb) - Jimmy Rivaldo Nampasnea; Sherly Adam; Carolina Tuhumury (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: The freedom of judges will be limited by statutory regulations (criminal procedural law), as stipulated in Law Number 8 of 1981 concerning Criminal Procedure Code (KUHAP). So that in deciding cases of rape crime, it must have a clear basis of consideration and can provide a deterrent effect on the perpetrator. The aim of the research is to examine and analyze the judge's legal considerations for the perpetrators of the crime of rape and to examine and analyze the imposition of sanctions on the perpetrators of the crime in the perspective of the purpose of punishment. In this legal research, the authors use Normative Juridical legal research which obtains data from literature studies in the form of laws, documents, books, magazines and other literature related to writing. The results of the research show that the judge's legal considerations for the perpetrators of the criminal act of rape study the decision number 451/Pid.B/2021/PN Amb, legally and convincingly proven guilty of committing the crime of rape. This is in accordance with the prosecutor's indictment, the defendant's statement, witness testimony, evidence, articles in the criminal law regulations and the defendant's background. The imposition of sanctions for the perpetrators of the crime of rape in the perspective of the purpose of sentencing is in accordance with sentencing and the defendant is given a criminal sanction of 10 (ten) years in prison, so what is the objective of sentencing and providing a deterrent effect on the perpetrators can be realized.